2009
DOI: 10.1016/j.mimet.2009.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Microscale sample preparation for PCR of C. difficile infected stool

Abstract: In this paper, we describe the design of a microfluidic sample preparation chip for human stool samples infected with Clostridium difficile. We established a polymerase chain reaction able to distinguish C. difficile in the presence of several other organisms found in the normal intestinal flora. A protocol for on-chip extraction of nucleic acids from clinical samples is described that can detect target DNA down to 5.0×10−3 ng of template. The assay and sample preparation chip were then validated using known p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…In order to demonstrate the concept of minimally instrumented nucleic acid extraction, we also utilized a portable version of the microfluidic nucleic acid extraction instrument and protocols developed previously in our laboratory [41], [42], [43], [44]. The portable version of this extraction system is called SNAP-System for Nucleic Acid Preparation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to demonstrate the concept of minimally instrumented nucleic acid extraction, we also utilized a portable version of the microfluidic nucleic acid extraction instrument and protocols developed previously in our laboratory [41], [42], [43], [44]. The portable version of this extraction system is called SNAP-System for Nucleic Acid Preparation.…”
Section: Methodsmentioning
confidence: 99%
“…The PPM columns ( Figure 2 ) were housed in unaltered FinnTip Universal 250 µl filter-less pipette tips (Thermo Fisher Scientific, Waltham, MA). These PPM columns were fabricated as previously described [41], [45] with some modification. Briefly, the pre-polymer monomer solution was prepared by mixing 125 µl Ethylene dimethacrylate (98%, EDMA), 125 µl Butyl methacrylate (99%, BUMA) (both Sigma-Aldrich, St. Louis, MO), 750 µl 1-dodecanol, and 8.0 mg azobisisobutyronitrile (AIBN).…”
Section: Methodsmentioning
confidence: 99%
“…The pH values of 3, 5.2, and 8 were chosen on the basis of the pK a values of the silica surface groups, the depurination of DNA (below pH 2), and the dissolution of silica (above pH 8) [30]. DNA adsorption and elution from the silica surface was quantified under conditions that mimic those commonly used in commercial kits and integrated POC diagnostic devices that isolate NAs from human samples [3133]. However, we incubated the DNA and silica particles significantly longer than most test protocols call for to make sure that equilibrium was reached.…”
Section: Introductionmentioning
confidence: 99%
“…Other improvements to consider will include on-board storage of primers and HDA buffer components, multiplexing to detect multiple target pathogens or strains and decreasing HDA reaction volumes on-chip. Although we used E. coli in broth medium for our proof-of-concept study, the same method of extraction with our μSPE chips has been shown previously to work in the background of complex biological samples of blood, urine, and stool for gram-negative bacteria such as E. coli and gram-positive bacteria such as Enterococcus faecalis , Bacillus subtilis and Clostridium difficile , and for RNA isolation from viruses and mammalian cells (Bhattacharyya and Klapperich 2006, 2008; Gillers et al 2009; Kulinski et al 2009; Mahalanabis et al 2009). Thus we anticipate that this integrated device may be applied for a wide variety of point-of-care diagnostic applications.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed methods on the manufacture of these channels and the μSPE columns are found in our previous reports of DNA extraction from bacteria in urine, blood and stool (Gillers et al 2009; Kulinski et al 2009; Mahalanabis et al 2009). The HDA was first performed in microtubes to establish that μSPE-extracted DNA was suitable for HDA and to determine the optimal concentrations and conditions for the reactions.…”
Section: Methodsmentioning
confidence: 99%